2018
DOI: 10.1177/1056789518792658
|View full text |Cite
|
Sign up to set email alerts
|

Parameter distribution characteristics of material fatigue life using improved bootstrap method

Abstract: The bootstrap method is mostly used to estimate statistical characteristics of small sample data. However, the limitations of the bootstrap method itself lead to a reduction in the reliability of small-sample estimates. In this article, an improved bootstrap method is developed to address this problem. In the statistically significant error range (the sample average error and the limit error of sampling) of the original single sample data, expanding the virtual test data that obey two distributions to overcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…In order to improve the reliability of fuel cell vehicle system, a comprehensive evaluation method considering uncertainty could be used 32 . The error circle could also be introduced into the improved bootstrap method to improve the credibility of the S‐N curve 33,34 …”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the reliability of fuel cell vehicle system, a comprehensive evaluation method considering uncertainty could be used 32 . The error circle could also be introduced into the improved bootstrap method to improve the credibility of the S‐N curve 33,34 …”
Section: Introductionmentioning
confidence: 99%
“…The two-dimensional joint probability density function of the load is shown in equations (27) and (28) Table 8. Common probability distribution.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…The mixed probability distribution is widely adopted in various fields including meteorological analysis, 25 signal processing, 26 environmental protection, 27 and material life estimate. 28 Combining structural health monitoring (SHM) data with reliability analysis programs, a mixture distribution model is used to accurately assess the reliability of monitoring structural components. 29 Wu et al 30 suggested an indirect probability model for reliability assessment of multi-body mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Under cyclic loading, a large number of engineering practices proved that the main failure form of mechanical parts is fatigue damage. 1,2 Most service structures on automobiles are subjected to cyclic loads, so fatigue damage and fracture of components is one of the main failure forms. Due to the complexity and unpredictability of the road conditions, the front stabilizer bar of the car is often impacted by the load cycles from the road surface.…”
Section: Introductionmentioning
confidence: 99%